Which is More Interesting Between Gamification, Share, and Like in Customer Engagement in Millennials and Generation Z? - Indry Sulistiawati; Rahmawati Rahmawati; Saida Zainurossaiamia ZA (International Journal Labs, 2022)
Background: Shopee is one of the major online retailers that offers a marketplace for exchanges of products and services between vendors and consumers, allowing for simple electronic transactions across networks and the internet. Shopee is not just a place for transactions; as it develops, it also offers a variety of conveniences for its users, such as making it simpler for users to complete daily tasks involving the purchase of goods and services, facilitating transactions, offering customers assistance with shopping-related issues, having game features that elicit strong emotions and offer numerous advantages, etc. 140 respondents were surveyed for this study, many of whom were Samarinda City Shopee users. Objective: This study aims to analyze which is more interesting between gamification, share, and like in customer engagement in millennials and gemerasi z. Method: By employing the PLS analysis technique to ascertain the influence between variables, this form of research is quantitative Result: The results of this study are broken down into ten hypotheses that explain how content marketing, gamification, and e-Women all significantly affect customer engagement, customer loyalty, and customer engagement—all of which are significantly mediated by customer engagement—and how content marketing, gamification, and e-Women significantly affect customer loyalty. Conclusion: Customer engagement, which is influenced by marketing strategies like content marketing, gamification, and e-WOM, has an impact on customer loyalty through the medium of customer engagement. This engagement is supported by quality and useful content to encourage positive comments on the content provided, and the presence of game features that offer rewards encourages customers to keep up their engagement in order to draw emotional customers who will be devoted to Shopee's goods and services.